2006
DOI: 10.1128/jcm.02311-05
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Neisseria gonorrhoeae in Amsterdam, The Netherlands, Shows Distinct Heterosexual and Homosexual Networks

Abstract: patients with a laboratory-confirmed diagnosis of gonorrhea at the Clinic for Sexually Transmitted Infections in Amsterdam, The Netherlands, were subjected to a questionnaire pertaining to sexual risk behavior and sexual partners in the 6 months prior to the diagnosis. The Neisseria gonorrhoeae isolates were all genotyped using PCR-restriction fragment length polymorphism of the porin and opacity genes. All patients with a completed questionnaire and genotyped isolates were included in the study. We obtained 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 22 publications
(28 reference statements)
1
38
2
Order By: Relevance
“…Membership of these subpopulations was not dependent on the intensity of individual risk behaviour but on identifiable geographical and sociodemographic factors. Further evidence for the existence of such sexual networks comes from recent molecular epidemiologic studies in London and Amsterdam, which showed that distinct strains of gonorrhoea caused geographically clustered infections in individuals with significantly different sociodemographic characteristics (Choudhury et al 2006;Kolader et al 2006;Risley et al 2007). We interpret this as further support for the concept that the transmission of gonorrhoea and possibly other STIs is in essence being maintained by geographically and demographically distinct core subpopulations, with such subpopulations comprising not only the cases observed in the studies mentioned (the clinical-epidemiologic perspective), but also the uninfected individuals belonging to the same sexual network, which could be defined by a combination of sociocultural and geographical characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Membership of these subpopulations was not dependent on the intensity of individual risk behaviour but on identifiable geographical and sociodemographic factors. Further evidence for the existence of such sexual networks comes from recent molecular epidemiologic studies in London and Amsterdam, which showed that distinct strains of gonorrhoea caused geographically clustered infections in individuals with significantly different sociodemographic characteristics (Choudhury et al 2006;Kolader et al 2006;Risley et al 2007). We interpret this as further support for the concept that the transmission of gonorrhoea and possibly other STIs is in essence being maintained by geographically and demographically distinct core subpopulations, with such subpopulations comprising not only the cases observed in the studies mentioned (the clinical-epidemiologic perspective), but also the uninfected individuals belonging to the same sexual network, which could be defined by a combination of sociocultural and geographical characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular typing can be used to explore the basis of the emergence of QRNG strains, and several methods have been used for typing gonococci (6,9,25). In recent years, sequence-based methods have been favored for molecular typing as they allow simple interlaboratory comparisons of isolates.…”
mentioning
confidence: 99%
“…Typing of Neisseria gonorrhoeae isolates has provided a valuable adjunct to contact tracing for reconstructing sexual networks (3,14) and for identifying individuals predicted to be in the same sexual network (2,6). Phenotypic typing methods for gonococci-for example, the combination of auxotype and serovar-lack sufficient discrimination for this purpose, but a number of more-discriminatory molecular methods have been developed.…”
mentioning
confidence: 99%